The Use of EMDR Therapy for Couples Considering Divorce: Theory and Practice - Luft, Toupey M. (Canadian Journal of Counselling and Psychotherapy, 2016)
Since its introduction in 1989, eye movement desensitization and reprocessing therapy (EMDR) has gained a solid body of evidence for its efficacious use in treating trauma and its effects. The process of divorce is likely to activate what is known as “small t” trauma reactions in each individual of the couple. “Small t” traumas are responses to common life difficulties such as divorce or unemployment, and usually bring out irrational cognitions and inadequate ability to cope with certain events. Recent years have seen a surge of interest in investigating how EMDR therapy may be used for these more common traumas that can have a strong impact on individuals and couples. In particular, this article outlines the use of EMDR with an expository case of a couple considering divorce after an affair. The article presents research support for EMDR as a psychotherapy model for both “capital T” and “small t” traumas. The expository case is considered, and clinical decision-making from an EMDR-based approach integrated with body-focused interventions is delineated. Finally, a call for future research is included.